The Triatoma phyllosoma species group (Hemiptera: Reduviidae: Triatominae), vectors of Chagas disease: Diagnoses and a key to the species - Rengifo-Correa, Laura; Juan Luis Téllez-Rendón, Juan Luis X; Esteban, Lyda; Huerta, Herón; Morrone, Juan J. (Zootaxa, 2021)
The Triatoma phyllosoma species group includes 17 species of kissing bugs, most of them implicated in the transmission of Chagas disease in the Americas. The species of this group are T. bassolsae Alejandre-Aguilar, Nogueda-Torres, Cortéz-Jímenez, Jurberg, Galvão & Carcavallo, 1999, T. brailovskyi Martínez, Carcavallo & Pelaez, 1984, T. dimidiata (Latreille, 1811), T. gerstaeckeri (Stål, 1859), T. gomeznunezi Martínez, Carcavallo & Juberg, 1994, T. hegneri Mazzotti, 1940, T. huehuetenanguensis Lima-Cordón, Monroy, Stevens, Rodas, Rodas, Dorn & Justi, 2019, T. indictiva Neiva, 1912, T. longipennis Usinger, 1939, T. mazzottii Usinger, 1941, T. mexicana (Herrich-Schaeffer, 1848), T. mopan Dorn, Justi, Dale, Stevens, Galvão, Lima-Cordón & Monroy, 2018, T. pallidipennis (Stål, 1872), T. phyllosoma (Burmeister, 1835), T. picturata Usinger, 1939, T. recurva (Stål, 1868), and T. sanguisuga (LeConte, 1855). The validity of some species of the group was uncertain, because of both cryptic species and hybrid occurrence. Species exhibiting these particularities were formerly classified in the T. dimidiata and T. phyllosoma complexes. Although we recognize the historical value of these species complexes, we do not recommend their further use. Instead, we recognize the T. phyllosoma species group here reviewed, considering the current knowledge of the systematics and reproductive behavior of the group. We implement the cohesion species concept, validating the species status of T. bassolsae, T. longipennis, T. mazzottii, T. pallidipennis, T. phyllosoma, and T. picturata. We also provide diagnoses, photographs and a taxonomic key including the recently described species.